Perbandingan Penggunaan Media Gambar Dengan Media Video Terhadap Hasil Belajar Matematika SDN 067241 MEDAN - Zahra, Aqila; Asyfa, Siti Aulina; Tinambunan, Nur Asiah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this study can prove the comparison of Mathematics learning outcomes with picture media or students taught with video media. This study was analyzed for 1 week to be precise, in October, with a sample of 60 class students. Precisely 30 grade IIA students who were given mathematics lessons using Image Media and 30 grade IIB students who were given Mathematics learning using Video Media, the selection of the research sample was carried out by a simple random sampling method based on calculations obtained from data that the average student learning outcomes through image media had an average of 57.97 with a standard deviation of 11.58, a median of 58.5 and a mode of 58. Furthermore, the learning outcomes of students taught through video media have an average of 74.37 with a standard deviation of 9.84, a median of 80 and a mode of 79.8. Based on the hypothesis test obtained by Table (19.292.002), there is a comparison of student learning taught using image media and video media.